2023
DOI: 10.1101/2023.12.07.570544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syndrome-informed phenotyping identifies a polygenic background for achondroplasia-like facial variation in the general population

Michiel Vanneste,
Hanne Hoskens,
Seppe Goovaerts
et al.

Abstract: Human craniofacial shape is highly variable yet highly heritable with genetic variants interacting through multiple layers of development. Here, we hypothesize that Mendelian phenotypes represent the extremes of a phenotypic spectrum and, using achondroplasia as an example, we introduce a syndrome-informed phenotyping approach to identify genomic loci associated with achondroplasia-like facial variation in the normal population. We compared three-dimensional facial scans from 43 individuals with achondroplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…While eventually achieving a comparable GWAS discovery rate to PCA, this convergence primarily resulted from the inclusion of more extreme facial examples, which were progressively less extreme. Nevertheless, while resemblance scores derived from syndromic and extreme facial examples may not yield the greatest number of loci in GWAS, studies [2224] have demonstrated that a targeted facial phenotyping resulted in GWAS loci that displayed a stronger link with disease etiology versus non-targeted phenotyping approaches. Therefore, facial traits derived from genetic conditions may facilitate the discovery of disease-related genes and pathways in future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While eventually achieving a comparable GWAS discovery rate to PCA, this convergence primarily resulted from the inclusion of more extreme facial examples, which were progressively less extreme. Nevertheless, while resemblance scores derived from syndromic and extreme facial examples may not yield the greatest number of loci in GWAS, studies [2224] have demonstrated that a targeted facial phenotyping resulted in GWAS loci that displayed a stronger link with disease etiology versus non-targeted phenotyping approaches. Therefore, facial traits derived from genetic conditions may facilitate the discovery of disease-related genes and pathways in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to investigate both typical-range and disease-associated variation in facial morphology, some studies employed a phenotyping method supervised by genetic conditions characterized by distinct facial features. Examples include resemblance scores to the facial archetype associated with Achondroplasia [22] and Pierre Robin Sequence [23] as well as resemblance scores to the distinctive facial endophenotype in unaffected family members of individuals with non-syndromic cleft lip [24]. The general idea of this approach is to directly measure the facial features that result from subtle variations within the same physiological pathways, which when disrupted result in distinct (sub-)clinical facial characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation